2018
DOI: 10.1111/liv.13873
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of hypercoagulability in patients with HCV‐related cirrhosis after treatment with direct‐acting antivirals

Abstract: DAAs therapy in HCV-related cirrhotic patients is associated with significant changes in thrombin generation suggesting a reversal of hypercoagulability particularly in Child's A patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…Using the near patient WB‐TG assay, we observed that the endogenous thrombin generating potential (ETPp) values of patients with cirrhosis, regardless of the presence/absence of TM, were in the same range as in healthy controls, suggesting that these patients had normal thrombin‐generating capacity. The standard PPP‐TG results add to the growing literature that hypocoagulable state is suggested when TG is tested without activating the protein C pathway, whereas hypercoagulable state is found when the function of the anticoagulant protein C pathway is included in TG by adding TM into the test . These results indicate that cirrhosis does not necessarily result in a hypocoagulable state as suggested by their lower procoagulant factor levels and prolonged PT and APTT, thus reinforcing that prophylactic administration of fresh‐frozen plasma according to their PT/APTT is not required …”
Section: Discussionmentioning
confidence: 55%
“…Using the near patient WB‐TG assay, we observed that the endogenous thrombin generating potential (ETPp) values of patients with cirrhosis, regardless of the presence/absence of TM, were in the same range as in healthy controls, suggesting that these patients had normal thrombin‐generating capacity. The standard PPP‐TG results add to the growing literature that hypocoagulable state is suggested when TG is tested without activating the protein C pathway, whereas hypercoagulable state is found when the function of the anticoagulant protein C pathway is included in TG by adding TM into the test . These results indicate that cirrhosis does not necessarily result in a hypocoagulable state as suggested by their lower procoagulant factor levels and prolonged PT and APTT, thus reinforcing that prophylactic administration of fresh‐frozen plasma according to their PT/APTT is not required …”
Section: Discussionmentioning
confidence: 55%
“…Patients' characteristics have been previously published . Briefly, 58 patients with HCV‐related cirrhosis were enrolled (M/F 38/20, mean age 59 years).…”
Section: Resultsmentioning
confidence: 99%
“…The study cohort has been recently described . Briefly, all consecutive patients with HCV‐related cirrhosis referred to the Multivisceral Transplant Unit and the Gastroenterology Unit of Padova University Hospital for anti‐HCV treatment with DAAs between September 2015 and March 2016 were eligible for enrolment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations